The inverse relationship between the non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio and testosterone in adult males in the United States: a cross-sectional study based on the NHANES database - Mei, Yangyang; Chen, Yiming; Wang, Xiaogang; Xu, Renfang; Xu, Rui; Feng, Xingliang (Frontiers in Endocrinology, 2025)
BackgroundTestosterone is a crucial hormone for male health, influencing metabolism, cardiovascular function, bone density, and cognitive abilities. Elevated non-HDL cholesterol to HDL cholesterol ratio (NHHR) has been implicated in lipid metabolism disorders, which may adversely affect testosterone levels. This study investigates the association between NHHR and testosterone levels in adult males, utilizing data from the National Health and Nutrition Examination Survey (NHANES).MethodsThis cross-sectional study analyzed data from 2,859 adult males from the NHANES cycles 2011-2016. Total testosterone levels were measured using isotope dilution liquid chromatography-tandem mass spectrometry (ID-LC-MS/MS). NHHR was calculated and analyzed as both a continuous variable and in quartiles. Multivariable linear and logistic regression models, adjusted for demographic, biochemical, lifestyle factors, and medical comorbidities, were used to assess the relationship between NHHR and total testosterone levels and the risk of testosterone deficiency (TD).ResultsHigher NHHR was significantly associated with lower total testosterone levels and increased risk of TD. In fully adjusted models, each unit increase in NHHR was associated with a decrease in total testosterone levels (β = -16.31, 95% CI: -26.58 to -6.04, P = 0.003) and an increased risk of TD (OR = 1.24, 95% CI: 1.07 to 1.44, P = 0.01). When NHHR was analyzed in quartiles, participants in the highest quartile (Q4) had significantly lower testosterone levels (β = -54.98, 95% CI: -86.21 to -23.74, P = 0.001) and a higher risk of TD (OR = 2.04, 95% CI: 1.20 to 3.49, P = 0.01) compared to those in the lowest quartile (Q1). Subgroup analyses confirmed these findings across different age groups, BMI categories, smoking status, and presence of comorbidities. Smooth curve fitting demonstrated a linear relationship among them.ConclusionOur study is the first to identify a significant association between elevated NHHR and both reduced total testosterone levels and increased risk of TD in a large, representative sample of adult American males. These findings suggest that NHHR could serve as a valuable marker for early identification of individuals at risk for testosterone decline and TD, enabling timely and targeted clinical interventions.